ORIGIN AND LIFE OF ELISABETH OF HUNGARY - Schwandtnerova, Monika; Csampai, Otto (European Scientific Journal, ESJ, 2013)
Saint Elizabeth of Hungary born probably at Pressburg in 1207. At 14, she married Ludwig IV., Landgrave of Thuringia and they had three children. He joined the Fifth Crusade and died in Otranto in 1227. She died at Marburg, Hesse in 17 November 1231 at the age of 24 and was canonized in 1235. Saint Elizabeth spent her life differently than most saints. She led a simple life, personally tended the sick and the poor, and spent long hours at prayer. She built the Franciscan hospital at Marburg and devoted herself to the care of the sick until her death.